Professional view of doctors on improving the organization of radiation research for cancer patients - S. Yu. Lomakov (Исследования и практика в медицине)
Purpose of the study. To form proposals for improving the organization of the radiology diagnostics service in Oncology. Materials and methods. In 2019, the opinion of radiation diagnostics doctors (n=230) on the availability and quality of radiation studies for cancer patients was studied. The obtained empirical data were statistically processed with the calculation of intensive and extensive indicators, average values (M±δ) with a risk of error of 0.05. The student's t-test was used to assess the statistical significance of differences. The original data had a normal distribution. Individual parameters of the research results were given a score. Results. Radiologists highly rated the quality of their primary specialization for working with cancer patients (4.6 ± 0.3 points) and further postgraduate education (4.2 ± 0.8 points), but 38.6% need to deepen this knowledge. The respondents indicated that patients are not sufficiently informed about radiation studies, including: about the methods (67.3%); about contraindications (34.3%); about the procedure for obtaining a conclusion (30.8%); about the established waiting times (21.7%); about the procedure for pre-registration (15.6%). 33.9% of doctors pointed to the unreasonableness of radiological examinations in certain cases in cancer patients. According to the respondents, it will improve the quality and availability of medical care for cancer patients: additional training of radiologists (70.0%) and clinicians (42.6%); equipping medical institutions (38.2%), a separate procedure for routing cancer patients to radiological research (44.7%); increasing the staff of radiologists (36.1%) and nurses (17.4%); using telemedicine technologies (31,7%); excluding cases of unjustified referral of patients to research (27.3%); uninterrupted operation of medical equipment (27.3%). Conclusion. The results of the study revealed systemic shortcomings in the organization of the radiation diagnostics service in providing medical care to patients with cancer, the elimination of which will improve the system of organizing medical care for them, improve its quality and accessibility.